Pretransplant human leukocyte antigen antibodies detected by single‐antigen bead assay are a risk factor for long‐term kidney graft loss even in the absence of donor‐specific antibodies. (14th June 2016) - Richter, Rudolf; Süsal, Caner; Köhler, Stefanie; Qidan, Sara; Schödel, Alicia; Holschuh, Lisa; Brzoska, Martin; Asbe‐Vollkopf, Aida; Büttner, Stefan; Betz, Christoph; Herrmann, Eva; Gauer, Stefan; et al.
Summary: Clinical relevance of ELISA‐ and single‐antigen bead assay (SAB)‐detected pretransplant HLA antibodies (SAB‐HLA‐Ab) for kidney graft survival was evaluated retrospectively in 197 patients transplanted between 2002 and 2009 at the University Clinic Frankfurt. Having adjusted for retransplantation and delayed graft function, a significantly increased risk for death‐censored graft loss was found in patients with pretransplant SAB‐HLA‐Ab [HR: 4.46; 95% confidence interval (CI): 1.47–13.48; P = 0.008]. The risk for increased graft loss was also significant in patients with pretransplant SAB‐HLA‐Ab but without SAB‐detected donor‐specific Ab (SAB‐DSA) (HR: 4.91; 95% CI of 1.43–16.991; P = 0.012). ELISA was not sufficient to identify pretransplant immunized patients with an increased risk for graft loss. In immunized patients, graft loss was predominantly present in patients who received transplants with a mismatch on the HLA‐DR locus. In conclusion, even if our study is limited due to small sample size, the results show an increased risk for long‐term graft loss in patients with pretransplant SAB‐HLA, even in the absence of DSA. SAB‐HLA‐Ab‐positive patients, being negative in ELISA or CDC assay, might profit from a well‐HLA‐DR‐matched graft and intensified immunosuppression.